2017
DOI: 10.1007/s11064-017-2322-9
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Attenuates Neurological Deficit after Intracerebral Hemorrhage by Inhibiting Apoptosis, Oxidative Stress and Neuroinflammation in Rats

Abstract: Intracerebral hemorrhage (ICH) can lead to brain damage and even death, and there is lack of effective therapeutic methods for treating ICH. Although recent studies have focused on the administration of metformin in treating stroke, there is no literature to support whether it can be used to treat ICH. Therefore, the aim of this study was to evaluate the possible effects of metformin on ICH and the underlying mechanisms of those effects. An ICH model was established in adult male Sprague-Dawley rats. Rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The apoptosis signalling‐regulating kinase 1 (ASK1) is known as a MAP3K that activates the JNK/p38 MAPK signalling pathway (Barros‐Minones et al, ; Tobiume et al, ). Previous studies have shown that the JNK/p38 MAPK signalling pathway was activated following ICH, leading to the release of pro‐inflammatory mediators and neuronal cell death (Ni et al, ; Qi et al, ). Interestingly, the JNK/p38 MAPK signalling pathway promoted NLRP1 inflammasome activation in neurons following ischaemic stroke in vivo and in vitro (Fann et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…The apoptosis signalling‐regulating kinase 1 (ASK1) is known as a MAP3K that activates the JNK/p38 MAPK signalling pathway (Barros‐Minones et al, ; Tobiume et al, ). Previous studies have shown that the JNK/p38 MAPK signalling pathway was activated following ICH, leading to the release of pro‐inflammatory mediators and neuronal cell death (Ni et al, ; Qi et al, ). Interestingly, the JNK/p38 MAPK signalling pathway promoted NLRP1 inflammasome activation in neurons following ischaemic stroke in vivo and in vitro (Fann et al, , ).…”
Section: Introductionmentioning
confidence: 99%
“…c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (p38 MAPK) that belong to the MAPK family have already been widely investigated for their roles in response to various stress stimuli [ 19 ]. Several studies have demonstrated that JNK and p38 MAPK signaling pathways were activated after ICH, leading to the upregulation of proinflammatory mediators including TNF-α, IL-6, and IL-1β [ 20 , 21 ]. A previous study indicated that activation of MC4R could significantly decrease the expression levels of JNK and p38 MAPK [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal studies have further demonstrated that long‐term metformin pretreatment can obviously alleviate the damage of ischemic stroke to brain tissue 12, 13, 14. In addition, metformin is also effective in treating global cerebral ischemia,15 intracerebral hemorrhage,16 epilepsy,17 Parkinson disease,18, 19 and Huntington disease 20. However, whether and how metformin treatment is effective in reducing brain injury after CA remain uninvestigated.…”
Section: Introductionmentioning
confidence: 99%